BIOLOGICAL ACTIVITY OF PURIFIED MANNOPROTEIN FROM BAKER’S YEAST AGAINST PSEUDOMONAS AERUGINOSA - Zainab Jawad Salman, Zainab Jawad Salman; Raghad Akram Aziz, Raghad Akram Aziz; Jehan Abdul Sattar Salman, Jehan Abdul Sattar Salman (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study aimed to evaluate the biological activity of mannoprotein purified from baker's yeast Saccharomyces cerevisiae available in local markets. The mannoprotein was extracted, purified and the emulsifying activity was detected at each step. The emulsifying activity of crude mannoprotein was 67.85%. The crude mannoprotein was partially purified by precipitation using cold ethanol and the emulsifying efficiency reached to 75%. Then it was completely purified using gel filtration chromatography with Sephadex G-100 gel, the purified mannoprotein had 37.61 mg/ml protein and 32.93 mg/ml carbohydrate with emulsifying activity 87.55%. Mannoprotein was characterized using FTIR and amino acid analysis which showed that the mannoprotein was glycoprotein. The antibacterial and antibiofilm activity of mannoprotein against Pseudomonas aeruginosa isolates from different clinical sources was tested and show very high effect in the reduction of bacterial growth with rate reached to 98.4%. Also, the mannoprotein inhibited the biofilm formation for bacterial isolates at different rates, the highest rate was 60.09%, while the rates of biofilm degradation were lower and reached to 21.12%. FE-SEM examination showed a reduction in biofilm formation.